HERMENEUTIKA HANS-GEORG GADAMER DAN SIGNIFIKANSINYA TERHADAP PENAFSIRAN AL-QURAN - Muh. Hanif (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
The paper discusses the introduction of hermeneutics, Gadamer's biography, Gadamer's hermeneutics and Quranic exegesis, and examples of interpreters using the Gadamer hermeneutics model. hermeneutics tried to grasp the meaning of the Quranic text. Meaning comes from the German